Triceps Fascial Tongue Exposure for Total Elbow Arthroplasty. Issue 2 (June 2015) - Marinello, Patrick G.; Peers, Sebastian; Styron, Joseph; Pervaiz, Khurram; Evans, Peter J.
<x xml:space="preserve">Abstract</x> During a posterior approach to the elbow, the triceps muscle body and tendon insertion must be addressed during exposure. Several methods exist including performing an olecranon osteotomy. The triceps fascial tongue exposure, originally described by Van Gorder in 1940, provides an excellent view of the joint while causing minimal trauma to the extensor mechanism facilitating tendon healing, and easy intraoperative conversion from fracture fixation to a total elbow arthroplasty if a fracture is not able to be reconstructed. Using a standard posterior approach to the elbow, a triceps tongue is created. A distally based flap of the triceps tendon approximately 10 cm long and 2 to 3 cm wide is created and a remnant of the tendon is kept on all sides to secure a meticulous repair with nonabsorbable figure-of-eight sutures at the conclusion of the case. In our case series, 29 patients underwent 30 total elbow arthroplasties. There were no triceps-related failures. This surgical technique is a useful alternative surgical exposure to the posterior elbow for fractures and arthroplasty.